Security Attacks in Vehicular Networks and Survey on Recent Developments in Detection and Protection Against Threats - G. Mahendran,; S. Murugeswari, (AG Volumes, 2022)
In today's automobiles, security is a primary issue. Among the numerous advantages provided by contemporary vehicle systems are reduced traffic congestion, improved safety, and decreased use of gasoline and diesel fuel. Personal information may be leaked and human lives put in jeopardy by security holes in automobile systems. Vehicle networks are vulnerable to a wide range of security risks, and this article aims to examine them all in relation to the network's cyber security. To help prevent these hazards, the study also provides a literature review of current practises in this area.